2020
DOI: 10.3390/fi12060108
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Evaluate Standards and Platforms within Cyber Threat Intelligence

Abstract: The cyber security landscape is fundamentally changing over the past years. While technology is evolving and new sophisticated applications are being developed, a new threat scenario is emerging in alarming proportions. Sophisticated threats with multi-vectored, multi-staged and polymorphic characteristics are performing complex attacks, making the processes of detection and mitigation far more complicated. Thus, organizations were encouraged to change their traditional defense models and to use and to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 42 publications
0
19
0
5
Order By: Relevance
“…The authors enhance previous CTI comparisons by emphasizing strengths, weaknesses, and structure as well as use cases for CTI formats [58]. Other current works reproduce CTI format analysis with similar evaluation criteria and results [59], [60] or extend research to the evaluation of CTI sharing platforms. In this respect, Bauer et al [61] identified the necessity of CTI standardization for information description and CTI sharing use cases within their non-functional platform criteria.…”
Section: B Related Workmentioning
confidence: 85%
“…The authors enhance previous CTI comparisons by emphasizing strengths, weaknesses, and structure as well as use cases for CTI formats [58]. Other current works reproduce CTI format analysis with similar evaluation criteria and results [59], [60] or extend research to the evaluation of CTI sharing platforms. In this respect, Bauer et al [61] identified the necessity of CTI standardization for information description and CTI sharing use cases within their non-functional platform criteria.…”
Section: B Related Workmentioning
confidence: 85%
“…This information can be shared amongst trusted stakeholders [46]. Different CTI platforms were evaluated in [47]. According to this paper, MISP is a reliable platform for CTI sharing.…”
Section: Related Workmentioning
confidence: 99%
“…Since its inception within military circles, MISP has grown into one of the leading open-source sharing platforms used by over 6000 organizations worldwide 1 . MISP is also one of the most studied platforms [14], [15], [16], characterized as holistic and applicable in diverse scenarios as well as flexible considering the compatibility with different formats [11].…”
Section: Context and Related Workmentioning
confidence: 99%
“…Furthermore, usability has been included as key evaluation criteria in recent frameworks for comparing the state-of-theart in CTI sharing platforms [11]. Nevertheless, despite this acknowledgment on the importance of UX in the context of CTI sharing platforms, empirical evidence on their usability, or perceived UX is scarce to non-existent.…”
Section: Introductionmentioning
confidence: 99%